The Role and Necessity of Sentinel Lymph Node Biopsy for Invasive Melanoma - Nakamura, Yasuhiro (Frontiers in Medicine, 2019)
Sentinel lymph node biopsy (SLNB) is a widely accepted procedure for melanoma staging and treatment. The development of lymphatic mapping and SLNB, which was first introduced in 1992, has enabled surgeons to detect microscopic nodal metastases and stage-negative regional nodal basins with low morbidity. SLNB has also facilitated the selective application of regional lymph node dissection for patients with microscopic nodal metastases, enabling unnecessary lymph node dissection. In contrast, recent major randomized phase III trials (DeCOG-SLT and MSLT–II trial) compared the clinical benefit of early completion lymph node dissection with observation after detecting microscopic nodal disease. The results of those studies indicated that there was no significant difference in the survival between the two groups, although regional control was superior after early completion lymph node dissection compared to that obtained after observation. Thus, the role and value of early completion lymph node dissection worldwide are currently very limited for patients with microscopic nodal disease. However, the use of SLNB is still controversial. Herein, we describe the current role and value of SLNB and completion lymph node dissection and discuss the major controversies as well as the favorable future outlook.